Interfaith Educational Collaboration Enhances Cultural Adaptation in Lombok and Bali - Fathurrahman Muhtar; Mohamad Abdun Nasir; Sudarsono; Hasniza Nordin (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study explores the collaborative role of religious educators in fostering interfaith harmony in Lombok and Bali, regions with diverse religious demographics.